Grúz vendégek a Magyar ATV-nél
Recording of a TV program entitled “Napi 120’” on Magyar ATV where the guests are Mikheil Saakashvili, former Minister of Justice, and Zurab Zhvania, former Chairman of the Parliament. They discuss, among other topics, their newly earned CEU Open Society Prize, Georgia’s status in world affairs and debate Georgia’s past and present problems. Reporter and interviewer: László Szőke.